Wards of Faerie - Brooks, Terry (New York Del Rey/Ballantine Books, 2013)
Tumultuous times are upon the world now known as the Four Lands. Magic and science are in conflict. The dwindling Druid order is threatened with extinction. But a long-forgotten diary comes to the attention of a druid and there can be no turning back. Whoever captures the Elfstones will surely hold the advantage in the devastating clash to come.
Reprint. Originally published: 2012
102177
Keywords: Shannara (Imaginary place); Elves; Druids; Good and evil; Fantasy fiction; Fiction